2016
DOI: 10.1111/cmi.12624
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and molecular genetic analysis of the cell wall salvage response ofAspergillus nigerto the absence of galactofuranose synthesis

Abstract: SummaryThe biosynthesis of cell surface‐located galactofuranose (Galf)‐containing glycostructures such as galactomannan, N‐glycans and O‐glycans in filamentous fungi is important to secure the integrity of the cell wall. UgmA encodes an UDP‐galactopyranose mutase, which is essential for the formation of Galf. Consequently, the ΔugmA mutant lacks Galf‐containing molecules. Our previous work in Aspergillus niger work suggested that loss of function of ugmA results in activation of the cell wall integrity (CWI) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 65 publications
1
18
0
1
Order By: Relevance
“…A. niger strain MA234.1 (transient ku70::amdS) (Park et al 2016 ) and its derivatives were grown at 30 °C using minimal medium (MM) (de Vries et al 2004 ) containing 25 mM xylose as a carbon source and either (MM-XA) or not (MM-X) containing 1.5% agar. Alternatively, strains were grown on Czapek Yeast Auto-lysate (CYA) agar (Frisvad and Samson 2004 ), Yeast Extract Sucrose (YES) agar (Frisvad and Samson 2004 ), or transformation medium (TM; MM containing 0.5% yeast extract, 0.2% casaminoacids, and 25 mM glucose, pH 6)(Kusters-van Someren et al 1991 ).…”
Section: Methodsmentioning
confidence: 99%
“…A. niger strain MA234.1 (transient ku70::amdS) (Park et al 2016 ) and its derivatives were grown at 30 °C using minimal medium (MM) (de Vries et al 2004 ) containing 25 mM xylose as a carbon source and either (MM-XA) or not (MM-X) containing 1.5% agar. Alternatively, strains were grown on Czapek Yeast Auto-lysate (CYA) agar (Frisvad and Samson 2004 ), Yeast Extract Sucrose (YES) agar (Frisvad and Samson 2004 ), or transformation medium (TM; MM containing 0.5% yeast extract, 0.2% casaminoacids, and 25 mM glucose, pH 6)(Kusters-van Someren et al 1991 ).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA extraction, RNA quality control, and RNA sequencing were performed at GenomeScan (Leiden, the Netherlands). Quality analysis of raw data was done as previously described (30). In brief, ~13 million reads of 150 bp were obtained from paired-end mode for each sample.…”
Section: Transcriptional Profilingmentioning
confidence: 99%
“…Moreover, we analyzed the role of Crh enzymes in the process of cell wall deficiency, by introducing a mutation in a gene required for cell wall galactomannan synthesis (Δ ugmA ) in the seven-fold crh knockout strain. A deletion of ugmA was previously shown to compromise cell wall integrity caused by a galactofuranose deficiency ( Damveld et al, 2008 ), and revealed upregulation of crhE in transcriptomic studies ( Park et al, 2016 ). Additionally, we assessed the relation between chitin to β-glucan cross-linking and α-1,3-glucan, by reducing cell wall α-glucan synthesis in both wild type and the seven-fold crh mutant.…”
Section: Introductionmentioning
confidence: 99%